Characterizing immune cell subsets of tumour infiltrating lymphocytes (TILs) in brain metastases. (15th October 2021) - Kalita-de Croft, Priyakshi; Chittoory, Haarika; Simpson, Peter; Lakhani, Sunil
Abstract: Aims: The heterogeneity of TILs are not well characterized in brain metastasis. To address this, we performed a targeted analysis of immune cell subsets in brain metastasis tissues. Method: We performed multiplex immunofluorescence (mIF) on a limited cohort of brain metastases arising from breast cancers (n=20). Using RNA-interference validated antibodies, we quantitated the subsets of immune cells in formalin-fixed paraffin embedded whole sections. The panel of proteins analyzed included PanCK, CD8, CD4, Vista and Iba1 and an average of 15000 cells per sample were analysed. We also analysed an independent publicly available cohort at the RNA level to corroborate our findings. Results: We found that increased density of tils (high>30%; low <30%) correlated with survival and they were two distinct phenotypes. The tumours with low tils had significantly higher expression of the immune-checkpoint molecule Vista in tumour cells (p<0.01) as well as in their microenvironment (p<0.001). Contrastingly, the brain metastatic tumours with high tils displayed higher expression of microglia. Low tils-tumours display CD8+ T-cells that exclusively co-express Vista (p<0.01) compared to high tils group where CD8+ T-cells significantly co-express Iba1 (p<0.05). Interestingly no definite phenotypes were observed in CD4+ T-cells. These results were also found in an independent cohort where Vista was a highly ranked gene within the CD8+ T-cell population. Conclusion: Variety of immune escape routes may be involved in brain metastasis. This may be executed by increasing the expression of T-cell inhibitory molecule Vista or by increased activated microglia which may release immunosuppressive cytokines. Further studies are required to provide mechanistic insights into these phenomena.